Effects of synovial macrophages in osteoarthritis - Zhao, Kun; Ruan, Jiaqi; Nie, Liuyan; Ye, Xiangming; Li, Juebao (Frontiers in Immunology, 2023)
Osteoarthritis (OA) is a common degenerative disease in mammals. However, its 24 pathogenesis remains unclear. Studies indicate that OA is not only an aging process that 25 but also an inflammation-related disease. Synovitis is closely related to the progression 26 of OA, and synovial macrophages are crucial participants in synovitis. Instead of being 27 a homogeneous population, macrophages are polarized into M1 or M2 subtypes in OA 28 synovial tissues. Polarization is highly associated with OA severity. However, the 29 M1/M2 ratio cannot be the only factor in OA prognosis because intermediate stages of 30 macrophages also exist. To better understand the mechanism of this heterogeneous 31 disease, OA subtypes of synovial macrophages classified by gene expression were 32 examined. Synovial macrophages do not act alone; they interact with surrounding cells 33 such as synovial fibroblasts, osteoclasts, chondrocytes, lymphocytes and even adipose 34 cells through a paracrine approach to exacerbate OA. Treatments targeting synovial 35 macrophages and their polarization are effective in relieving pain and protecting 36 cartilage during OA development. In this review, we describe how synovial 37 macrophages and their different polarization states influence the progression of OA. We 38 summarize the current knowledge of the interactions between macrophages and other 39 joint cells and examine the current research on new medications targeting synovial 40 macrophages. 41Osteoarthritis (OA) is a degenerative joint disease caused by chronic inflammation 43 in cartilage, subchondral bone and synovium. In osteoarthritic joints, major 44 删除了: among …n mammals. However, its pathogenesis remains